Traditional Food Plants Cultivated and Managed in Home Gardens in South Africa’s Eastern Cape Province. - Maroyi, Alfred (Asian Journal of Agriculture and Rural Development, 2022)
This study aimed to document the diversity of traditional food plants in South Africa’s Eastern Cape province. The survey was carried out in six local municipalities in the province, between March 2016 and September 2020. Information on the socio-economic characteristics of the informants and on traditional food plants collected from the wild and cultivated and managed in home gardens was recorded using questionnaires, personal observations, and guided field walks with 145 informants. A total of 58 edible plants belonging to 46 genera and 29 families were recorded. The plant families with the largest number of species were Solanaceae (six species), followed by Amaranthaceae and Asteraceae (five species each), Rosaceae (four species), and Apiaceae, Cactaceae, and Fabaceae sensu lato with three species each. The main uses of the documented species were edible fruits (56.9%), leafy vegetables (29.3%), and edible tubers (12.1%). Species that were categorized as valuable, with relative frequency of citation (RFC) values exceeding 0.3, were Solanum tuberosum, Allium cepa, Zea mays, Beta vulgaris, Cucurbita moschata, Brassica oleracea, Spinacia oleracea, Cucurbita maxima, Daucus carota, and Lycopersicon esculentum. The findings highlight the significance of edible plant species to the well-being of local communities in the Eastern Cape province within the context of food provisioning.